Consequences of Whole-Genome Triplication as Revealed by Comparative Genomic Analyses of the Wild Radish Raphanus raphanistrum and Three Other Brassicaceae Species - Moghe, Gaurav D. (American Society of Plant Biologists, 2014)
Polyploidization events are frequent among flowering plants, and the duplicate genes produced via such events contribute significantly to plant evolution. We sequenced the genome of wild radish (Raphanus raphanistrum), a Brassicaceae species that experienced a whole-genome triplication event prior to diverging from Brassica rapa. Despite substantial gene gains in these two species compared with Arabidopsis thaliana and Arabidopsis lyrata, ∼70% of the orthologous groups experienced gene losses in R. raphanistrum and B. rapa, with most of the losses occurring prior to their divergence. The retained duplicates show substantial divergence in sequence and expression. Based on comparison of A. thaliana and R. raphanistrum ortholog floral expression levels, retained radish duplicates diverged primarily via maintenance of ancestral expression level in one copy and reduction of expression level in others. In addition, retained duplicates differed significantly from genes that reverted to singleton state in function, sequence composition, expression patterns, network connectivity, and rates of evolution. Using these properties, we established a statistical learning model for predicting whether a duplicate would be retained postpolyploidization. Overall, our study provides new insights into the processes of plant duplicate loss, retention, and functional divergence and highlights the need for further understanding factors controlling duplicate gene fate.